Research on Spatial Deformation of Flexspline with Variable Thickness Tooth Ring - Yuqi Wang; Xiaoxia Chen; Jingzhong Xing; Yunpeng Yao (Jixie chuandong)
Crowned tooth can improve the meshing state between tooth surfaces and enhance the load capacity of harmonic gears. In order to reveal the deformation law of the flexspline with variable thickness of tooth ring formed by the radial modification of drum shape，a theoretical method of spatial deformation of the gear with variable neutral layer radius is proposed. The formulas of radial，circumferential and angular displacements of the neutral line of the gear ring with the axial midface radius changing are derived. A parametric solid unit element finite element model of cup type flexspline with real tooth profile is established，and the neutral line deformation in the forward，middle and back cross sections of the tooth ring is calculated by contact analysis. The finite element results of each section of the tooth ring agree well with the theoretical values. The spatial deformation characteristics of variable thickness tooth ring are studied by comparing with the model of equal thickness tooth ring. The results show that the nonlinear characteristics of the generatrix are aggravated by the variable thickness ring. The nonlinear characteristics of the generatrix in the long axis region from the middle section to the back section and the generatrix in the short axis region from the front section to the middle section are more significant.